CONSUMERS AND COSMETICS - BUYING PATTERN ANALYSIS IN ERODE CITY - Kalaiselvi, Dr.(Mrs) S (IJRDO -Journal of Computer Science Engineering, 2015)
In olden days people spend a lot of time in search of herbs to extract their benefits in order to safeguard themselves from various health hazards. In those days, they relied only upon natural herbs for healing. People in today’s world are leading very busy life that they do not really have time to spend on their external appearances. There are a thousand varieties of herbs that are being used for beauty care and medicine purpose. Examples of such herbs are Neem, Amla,Tulsi, Gooseberries, Sandalwood, Saffron and Green tealeaf etc. People used these herbs as their cosmetics to satisfy the needs of the consumers, now there are a number of cosmetic companies in the market which produces both chemical as well as Ayurveda bases cosmetic products. There are huge varieties of brand available in the market. Due to the technical advancement and other industrial development in the country, there is also a lot of pollution causing harm to internal and external parts of the body. Skin is the most affected part in the human body due to environmental pollution. Even though there are many chemical based cosmetics, people feel that these types of products cause more harm to the skin. Ayurveda products are usually made of natural herbs with very minimum amount of chemicals and are less harmful to the skin, which would reduce the side effects. Face is the reflection of an